1994
DOI: 10.1007/bf00175943
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide induced early biochemical changes in lung lavage fluid and alterations in lavage cell function

Abstract: The present investigation evaluated the changes in bronchoalveolar lavage fluid (BALF) biochemical constituents and indices of bronchoalveolar lavage cell functions to detect early lung injury in rats following intraperitoneal administration of cyclophosphamide (CP). Rats were exposed to a single intraperitoneal injection of CP (200 or 300 mg/kg body weight). Experimental and control rats were sacrificed at various time intervals (2, 3, 5, 7, 11, 21, and 42 days after cessation of exposure), and lung lavage wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 39 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…This could consequently lead to higher levels of GSSG and/or depletion of GSH. Cyclophosphamide can cause lung injury and has also been shown to deplete glutathione stores (11,30,42), increase the generation of reactive oxygen species by alveolar macrophages (12), inhibit prostaglandin E 2 production by macrophages (11), and modulate BAL cell populations (12). Acrolein, a cyclophosphamide metabolite, can also react directly with glutathione, forming irreversible conjugates (18).…”
Section: Discussionmentioning
confidence: 99%
“…This could consequently lead to higher levels of GSSG and/or depletion of GSH. Cyclophosphamide can cause lung injury and has also been shown to deplete glutathione stores (11,30,42), increase the generation of reactive oxygen species by alveolar macrophages (12), inhibit prostaglandin E 2 production by macrophages (11), and modulate BAL cell populations (12). Acrolein, a cyclophosphamide metabolite, can also react directly with glutathione, forming irreversible conjugates (18).…”
Section: Discussionmentioning
confidence: 99%
“…A number of chemicals were shown to affect GSH levels in BALF and plasma. For example, Venkatesan and Chandrakasan (1994) demonstrated that cyclophosphamide caused decreases in GSH in BALF in rats. Hyperoxia produced significant decreases in GSH in BALF in rats (Stenzel et al, 1993).…”
mentioning
confidence: 99%
“…However, this level of protection was transient, since 2 d of exposure no longer diminished the level of ozone-induced permeability damage. Although the level of cyclophosphamide treatment used in this study did not result in any observable lung damage or inflammation in the absence of ozone exposure (Figures 1 and 3) (Venkatesan & Chandrakasan, 1994), such pretreatment might have interfered with the proliferate repair of ozone-damaged epithelium that begins around 2 d from the onset of exposure (Bassett & BowenKelly, 1986;Choi et al, 1994;Evans et al, 1976).…”
Section: Figure 4 Recoveries Of (A) Neutrophils and (B) Albumin By Bmentioning
confidence: 96%